Instructions for fruit fly trappers: a manual of techniques used for the 1986-87 surveys in Grenada and St. Vincent and the Grenadines - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
60 páginas